A Small Increase in Serum Creatinine within 48 h of Hospital Admission Is an Independent Predictor of In-Hospital Adverse Outcomes in Patients with ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention: Findings from the Improving Care for Cardiovascular Disease in the China Project - Jiajia Zhu; Wenxian Liu; Jiang Li; Changsheng Ma; Dong Zhao (Cardiology Research and Practice)
Background. Acute kidney injury (AKI) is a common complication of percutaneous coronary intervention (PCI) that has been associated with high morbidity and mortality in patients with STEMI. Acute tubular damage may be reflected by serum creatinine (Scr) values that do not meet the criteria for AKI. Methods. This analysis included 19,424 patients from the Improving Care for Cardiovascular Disease in China, Acute Coronary Syndrome Project (n = 5,221 (36.8%), patients with a small increase in Scr within 48 h of hospitalization; n = 14,203 patients with no increase in Scr). The primary outcome was the incidence of major adverse cardiovascular events (MACE). Secondary outcomes included the incidence of massive hemorrhage, in-hospital death, atrial fibrillation, heart failure, cardiogenic shock, cardiac arrest, and stroke. Logistic regression analysis was used to evaluate associations between a small increase in Scr within 48 h of hospitalization (>0.1 to <0.3 mg/dl) and MACE or massive hemorrhage during hospitalization. Results. Patients with a small increase in Scr within 48 h of hospitalization were significantly more likely to experience MACE (11.2% vs. 9.1%; P<0.001) or massive hemorrhage (3.2% vs. 2.2%; P<0.001) compared to patients with no increase in Scr, but there was no significant difference in in-hospital mortality (0.8% vs. 0.9%; P=0.301). Logistic regression analysis showed that a small increase in Scr within 48 h of hospital admission was a risk factor for MACE (OR, 1.168; 95% CI, 1.044–1.306; P=0.006) or massive hemorrhage (OR, 1.413; 95% CI, 1.164–1.715; P<0.001). Other risk factors included age ˃65 years, history of heart failure, use of glycoprotein IIb/IIIa inhibitors, aspirin or ACEI/ARB, LVEF <40%, Killip class III-IV, and increased SBP and heart rate. Conclusion. A small increase in Scr during hospitalization in patients with STEMI undergoing primary PCI that does not meet the criteria for AKI is a risk factor for in-hospital adverse outcomes. This effect is maintained in patients with normal Scr at hospitalization. Trial Registration. Clinical trial registration: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02306616.